Heterogeneous seeded growth: synthesis and characterization of bifunctional Fe 3O 4/ZnO core/shell nanocrystals - Huang, N.; Chiu, W.; Khiew, P.; Cloke, M.; Isa, D.; Lim, H.; Tan, T.; Radiman, S.; Abd-Shukor, R.; Hamid, M.A.A.; Chia, C. (2010)
In the present study, Fe 3O 4/ZnO core/shell nanocrystals (NCs) are synthesized via seed-meditated growth approach in nonhydrolytic condition. The controlling process of thermal pyrolysis of zinc acetate (ZnAc) renders a condition to overgrow ZnO layer on the surface of Fe 3O 4 NCs (seeds). The transmission electron microscope (TEM) micrograph shows that Fe 3O 4/ZnO NCs are spherical in shape, highly monodispersed, and exhibiting responding shell thickness by varying the mole ratio of seed to shell precursor. The X-ray powder diffraction patterns (XRD) for Fe 3O 4/ZnO NCs reveal the coexistence of both Fe 3O 4 and ZnO crystal structures, which the patterns can be well indexed with the standard powder diffraction patterns of both materials. The NCs exhibit superparamagnetism corresponding to an external magnet field provided by vibrating sample magnetometer (VSM) and show red-shift phenomenon under UV excitation at room temperature. The NCs are magnetically separable upon application of 0.6 T magnet, which shows that high potentiality of the NCs to be used as regenerable catalyst material. Â© 2010 American Chemical Society.